Metacognition in Problem-based Learning (PBL) groups - Vargas, Adriana (2017)
Group learning is a process that involves cognitive functions mobilization and develops skills necessary throughout life. Problem-Based Learning (PBL), a proposal of group learning, emphasizes the cognitive development and may make the metacognition stronger. The objective was to answer the questions: 1) is PBL a methodology that involves metacognition development? 2) can we relate metacognition studies on group context to PBL? State of the art researches over the theme were realized, between 2010 – 2015, containing the terms metacognition and Problem-based Learning, in CAPES portal journals. Eight researches were selected because they describe empirical evidences of metacognition in PBL groups. PBL can be applied to studies group learning and metacognition, by mobilizing knowledge, awareness and self-control.